PROTOTYPE KOTAK PENYIMPANAN UANG MENGGUNAKAN SESOR WARNA BERBASIS MIKROKONTROLLER ARDUINO UNO - zulkarnaen zulkarnaen; Yudi Sutaryana; Suryati Suryati (Badan Penelitian dan Pengabdian Masyarakat (BP2M) STMIK Syaikh Zainuddin NW Anjani, 2025)
Digital wallets and banks are available, but many still use safe deposit boxes or piggy banks. This intake of pigs is required by various groups, from children to adults, as a means of saving, home decoration and toys. However, ceramic or plastic pig banks are easy to break, so many people convert to banks for safety. Advances in microcontroller technology have enabled the development of safe and intelligent cash deposit boxes. This microcontroller-based box can use the TCS 3200 color sensor and PIN or password system to protect your money from theft and unauthorized access. According to Syafii Antonio, Islam is recommended for future planning and Islamic emergency savings. A bad economy can lead to crimes such as ice cream pigeon theft, which is rarely safe. Technology integration allows safe deposit boxes to be linked to digital financial solutions, increasing the security and efficiency of cash management.